BIMBINGAN PRIBADI-SOSIAL UNTUK SISWA YANG MEMILIKI TINGKAT KEDISIPLINAN RENDAH - N. Ica Warnisa; Tita Rosita (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
The purpose of this study is to analyze problems in student discipline through Personal and Social Guidance Services that focus on student interaction in socializing at school in order to improve student discipline. The research method used is qualitative research that is literature study (library research). Based on the results of literature study, it is found that personal social guidance services can improve student discipline. Personal social guidance services can solve personal and social problems canalso help students in (a) change towards growth, (b) understand themselves fully and fully, (c) learn to communicate healthier, (d)practice new, healthier behaviors, (e) learning to express themselves fully and intact, (f) how individuals (students) can survive, and (g) relieving dysfunctional symptoms.Keywords: social personal guidance, discipline